China and the Asian economies interactive dynamics, synergy and symbiotic growth - Das, Dilip K. 1945- (Routledge, 2014)
"This book analyzes the emergence of Asian economies, followed by China, as an economic growth pole of enormous significance. Notwithstanding the diversity in the region, rapid growth was instrumental in integrating the Asian economies initially in a market-led manner and this book explores the interactive dynamics and the process of integration in the region".